2012
DOI: 10.1371/journal.pone.0040800
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis Quantifies Gait Abnormalities Associated with Lameness in Broiler Chickens and Identifies Evolutionary Gait Differences

Abstract: This is the first time that gait characteristics of broiler (meat) chickens have been compared with their progenitor, jungle fowl, and the first kinematic study to report a link between broiler gait parameters and defined lameness scores. A commercial motion-capturing system recorded three-dimensional temporospatial information during walking. The hypothesis was that the gait characteristics of non-lame broilers (n = 10) would be intermediate to those of lame broilers (n = 12) and jungle fowl (n = 10, tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 34 publications
2
40
1
Order By: Relevance
“…Comparing the gait of commercial strain and jungle fowl, Caplen et al (2012) found that broiler genetic strains present an unbalanced body due to the intense genetic selection for additional breast muscle (pectoral hypertrophy). Fast-growth birds develop compensatory gait adaptations to minimize energy expenditure that triggers high-lameness prevalence within commercial flocks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the gait of commercial strain and jungle fowl, Caplen et al (2012) found that broiler genetic strains present an unbalanced body due to the intense genetic selection for additional breast muscle (pectoral hypertrophy). Fast-growth birds develop compensatory gait adaptations to minimize energy expenditure that triggers high-lameness prevalence within commercial flocks.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology of observing EC related to their stance behavior might not be sufficient to estimate bird welfare. It has been reported that birds with little genetic selection pressure have a more upright posture, while modern broilers present a larger pectoral muscle mass and increased meat yield, tending to bow forward during the stance phase (Havenstein et al, 2003;Schmidt et al, 2009;Caplen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, sudden death syndrome (Govaerts et al, 2000) and ascites (Kalmar et al, 2013;Wideman et al, 2013) are wellknown problems in these broilers, in addition to low immunity and disease resistance . Moreover, increased pressure on legs and hips leads to limb abnormalities, which reduces the ability to move (Caplen et al, 2012). Ultimately, mortality and welfare are also associated with broiler rapid growth (Leeson and Summers, 2001;Dawkins and Layton, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Multirow computed tomography scanners (MCT) and magnetic resonance imaging (MRI) have been significantly improved, and today enable the diagnosis of various types of diseases. The influence of these diseases on locomotion disorders of poultry have been studied using optical 3D techniques (Caplen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%